Impact of knowledge management capabilities on new product development performance through mediating role of organizational agility and moderating role of business model innovation - Idrees, Hisham; Hynek, Josef; Xu, Jin; Akbar, Ahsan; Jabeen, Samrena (Frontiers in Psychology, 2022)
In several studies knowledge is witnessed as one of the foundations of long-term competitive edge and is also basic source of new product development (NDP) performance. The aim of current study is to investigate the role of knowledge management capabilities (KMC) in new product development performance with mediating role of organizational agility. Additionally, this study also intends to examine the moderating role of business model innovation on the relationship of KMC with organizational agility. This study is conducted on Chinese automobile sector and the NPD project managers, supervisors and engineers of the sector were the responded of the study. Survey questionnaire was used to collect the data from 201 respondents and data was analyzed by using Smart PLS 3 software. Findings of this research although limited to automobiles industry but indicate that knowledge sharing, and knowledge application have significant and positive effect on new product development. Organizational agility significantly mediates the relationship of KMC with NPD. The results found that business model innovation has significant moderating role on the relationship of KMC and organizational agility. Moreover, the results of this study will assist the managers in developing modern competitive business environment by implicating KMC in the process of NPD. Lastly, organizations may improve sustainability of their product and their overall performance by using organizational agility and modern ways of value delivery.